Interobserver Variability and Diagnostic Performance in US Assessment of Thyroid Nodule According to Size - Park, S. J.; Park, S. H.; Choi, Y. J.; Kim, D. W.; Son, E. J.; Lee, H. S.; Yoon, J. H.; Kim, E.-K.; Moon, H. J.; Kwak, J. Y. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: To evaluate the interobserver variability for US assessments of thyroid nodules and analyze the diagnostic performances of US assessments in thyroid nodules according to nodule size.Materials and Methods: This was an IRB-approved retrospective study with waiver of informed consent. A total of 400 surgically-confirmed thyroid nodules were included. Nodules were divided into 4 groups by size; group 1 (nodule size < 5 mm), group 2 (5 mm ≤ nodule size < 10 mm), group 3 (10 mm ≤ nodule size < 20 mm), and group 4 (nodule size ≥ 20 mm). Three experienced (7 – 10 years) radiologists retrospectively reviewed the US images. Agreement of each US descriptor and final US assessment, and diagnostic performances were calculated in each group and compared. Results: Composition represented substantial or good agreement (k = 0.719 – 0.89). Margin showed the lowest agreement (k = 0.322 – 0.365). Individual kappa values for final assessment according to nodule size were as follows: group 1 (k = 0.674), group 2 (k = 0.596), group 3 (k = 0.674), and group 4 (k = 0.673). Specificity, PPV, and accuracy were significantly different among the groups with different size (p value < 0.05) and lowest in group 1. NPV, specificity, PPV and accuracy except PPV of observer 3 increased with nodule size (p < 0.05). Conclusion: Interobserver agreements were relatively good (k = 0.637) in final US assessment regardless of nodule size in experienced radiologists. High false-positive rate was observed in US assessment in nodules less than 5 mm in maximum diameter.
Keywords: head/neck; tumor; ultrasound